Shock and Awe: Successful Revascularization with Intravascular Lithotripsy in Recurrent ST-Elevation Myocardial Infarction Secondary to Stent Under-Expansion - Pramod Kumar Ponna; Akhilesh Gonuguntla; Ramya Krishna Botta; Sruthi Kotaru; Tim A. Fischell; Adnan Alexander Kassier; Yashwant Agrawal (Methodist DeBakey Cardiovascular Journal)
We report a case of recurrent ST-segment elevation myocardial infarction (STEMI) due to a previously implanted under-expanded stent with in-stent thrombosis refractory to traditional interventional techniques. We underscore the utility of bail-out shockwave intravascular lithotripsy to tackle previously under-expanded stents in this acute setting.